A method for preparing a conductive carbon nanotube hollow fiber membrane that resists membrane fouling and its application in water treatment by electrochemical coupling
By adopting conductive carbon nanotube hollow fiber membranes in membrane separation technology and combining electrochemical coupling technology, the serious problem of membrane pollution in traditional membrane separation technology is solved, and efficient anti-pollution performance and membrane pollution removal effect are achieved, improving the The service life and water yield of the membrane are obtained.
Patent Information
- Application Number
- CN202410522140.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-04-28
AI Technical Summary
Traditional membrane separation technology has serious membrane pollution in water treatment, resulting in reduced membrane flux and poor flux recovery efficiency, thereby reducing water production efficiency, increasing operating costs and shortening membrane service life.
Using conductive carbon nanotube hollow fiber membranes, a secondary crosslinking network is constructed with pyrrole and maleimide and carbon nanotube base membrane to form a membrane separation layer with good anti-pollution ability, and electrochemical coupling is carried out during the separation process. Apply voltage to achieve enhanced containment and removal of membrane pollution.
It significantly improves the anti-pollution performance of the membrane and the membrane pollution removal performance during the backwashing process, extends the service life of the membrane, improves the water production rate and the operating stability of the membrane system, and reduces operating costs.
Smart Images

Figure CN118179281B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane separation and water treatment, and specifically relates to a method for preparing a conductive carbon nanotube hollow fiber membrane resistant to membrane pollution and the application of electrochemical coupling in water treatment. Background Art
[0002] Membrane separation technology is a modern technology for deep treatment of water and wastewater. The research and development of new membrane materials and their application methods are crucial to promoting the development of membrane separation technology.
[0003] At present, the traditional membrane separation technology still has serious membrane pollution problems in actual water treatment engineering applications. Membrane pollution refers to the phenomenon that during the membrane separation process, due to the accumulation of solutes, microorganisms or other particulate matter on the membrane surface or in the pores, the membrane flux is reduced and the flux recovery efficiency is poor, which ultimately reduces the water production efficiency of the membrane unit, makes the operation difficult, shortens the service life of the membrane and increases the operating costs. The preparation of separation membranes with good anti-pollution performance is the key to improving the operating efficiency of the membrane. Carbon nanotubes have a super-hydrophobic and smooth surface formed by the lattice structure of carbon atoms, which can reduce the adsorption of pollutants. Therefore, it is possible to obtain good anti-pollution performance by using carbon nanotubes as the basic material to prepare separation membranes. However, the traditional method of using carbon nanotubes to prepare separation membranes is often to dope carbon nanotubes as supplementary materials in organic separation membranes. The carbon nanotubes are filled with macromolecular polymers, and their surface hydrophobic properties cannot be exerted, which reduces their effectiveness in curbing membrane pollution. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a conductive carbon nanotube hollow fiber membrane that resists membrane fouling and the application of electrochemical coupling in water treatment. The conductive carbon nanotube hollow fiber membrane that resists membrane fouling is prepared by constructing a secondary cross-linked network of a carbon nanotube-based membrane with pyrrole and maleimide, and has excellent membrane fouling resistance. With the hollow fiber as the working electrode, voltage is applied during the separation process and backwashing process to achieve enhanced containment and removal of membrane fouling.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] In one aspect, the present invention provides a method for preparing a conductive carbon nanotube hollow fiber membrane that is resistant to membrane pollution, comprising the following steps:
[0007] (1) Preparation of spinning solution
[0008] Add purified carbon nanotubes, maleimide crosslinker and polyvinyl butyral ester to the solvent, stir evenly at room temperature to obtain solution A, then add polyvinyl butyral ester and maleimide crosslinker under the condition of constant temperature oil bath of 80-100° C., stir until completely dissolved, and obtain spinning solution;
[0009] (2) Preparation of basement membrane
[0010] Using water as the spinning core liquid and the spinning liquid as the spinning shell liquid, the core liquid and the shell liquid are controlled to pass through the spinning head at the same time, and then enter the coagulation bath to be pulled into a film, and then dried to obtain a base film;
[0011] (3) Pretreatment of base film by immersion and pulling
[0012] At room temperature, the base film is immersed and pulled in an acetonitrile solution of ferric chloride or ferric sulfate, and after drying, a base film containing an oxide layer is obtained;
[0013] (4) Secondary crosslinking of conductive polymer and maleimide crosslinker
[0014] The maleimide crosslinking agent is mixed with the pyrrole monomer to obtain a mixed solution. A base film containing an oxide layer is placed on the mixed solution by a gas phase polymerization method, and the base film is placed in a vacuum drying oven. The base film is polymerized and crosslinked at 80 to 100° C. for 120 to 180 minutes. The base film is immersed in an acetonitrile solution after cooling, and a conductive carbon nanotube hollow fiber membrane is obtained after drying.
[0015] In the above technical scheme, further, in step (1), the purified carbon nanotubes are single-walled carbon nanotubes or multi-walled carbon nanotubes, the purity of which is greater than 96%, and the content of oxygen-containing functional groups is less than 0.5wt%; the maleimide crosslinking agent is a mixture of one or more of maleimide, N-(4-anilinophenyl)maleimide, N-phenylmaleimide, N,N′-(1,3-phenylene)bismaleimide, and N,N′-(4,4′-methylenediphenyl)bismaleimide; the molecular weight of the polyvinyl butyral ester is 20,000 to 300,000; and the solvent is a mixture of one or two of N,N-dimethylformamide and N,N-dimethylacetamide.
[0016] In the above technical solution, further, in step (1), the diameter of the purified carbon nanotubes is 5 to 15 nm.
[0017] In the above technical solution, further, in step (1), the mass fraction of the solute in the solution A is 5-15%, and the mass fraction of the solute in the spinning solution is 20-50%.
[0018] In the above technical solution, further, in step (1), the mass ratio of the purified carbon nanotubes, polyvinyl butyral ester and maleimide in the spinning solution is 40-100:100:5-10.
[0019] In the above technical scheme, further, in step (2), the coagulation bath adopts 50-100% acetonitrile solution, and the temperature of the coagulation bath is 25-60°C; the flow rate ratio of the core liquid to the shell liquid is 0.5-3:1; the pulling speed is the same as the shell liquid extrusion speed, and the pulling speed is 0.2-1m / min; the drying temperature is 80-100°C.
[0020] In the above technical scheme, further, in step (3), the mass fraction of the solute in the acetonitrile solution of ferric chloride or ferric sulfate is 2-5%; the immersion time of the base film in the acetonitrile solution is 5-20 minutes, and the pulling speed after immersion is 1-3 mm / s; the drying time is 30-120 minutes.
[0021] In the above technical scheme, further, in step (4), the mass ratio of the pyrrole monomer solution to the base film is 0.25 to 1:1; in the mixed solution, the mass fraction of the maleimide crosslinker is 0.5 to 2%; the maleimide crosslinker is a mixture of one or more of maleimide, N-(4-anilinophenyl)maleimide, N-phenylmaleimide, N,N′-(1,3-phenylene)bismaleimide, and N,N'-(4,4'-methylenediphenyl)bismaleimide; the environmental vacuum degree of the polymerization crosslinking is >95%; the immersion time is 5 to 10 minutes; and the mass fraction of the acetonitrile solution is 50 to 100%.
[0022] Another aspect of the present invention provides a conductive carbon nanotube hollow fiber membrane resistant to membrane pollution obtained by the above-mentioned preparation method.
[0023] The present invention also provides a water treatment method of a conductive carbon nanotube hollow fiber membrane and electrochemical coupling, wherein the above-mentioned hollow fiber membrane is used as a membrane electrode. During the water treatment process, a voltage is applied to the hollow fiber membrane, the voltage is 0 to 10V and is not 0, the filtration form is cross-flow filtration, and the cross-flow flow rate is 0.05 to 0.1 m / s; during the backwashing process, a voltage is applied to the hollow fiber membrane, the voltage is 0 to 10V and is not 0, and the cross-flow flow rate is 1.5 to 3 times the flow rate during filtration.
[0024] In the above technical solution, further, the water treatment method specifically comprises the following steps:
[0025] a. Encapsulate the hollow fiber membrane in the membrane assembly. The hollow fiber membrane is used as the working electrode. Both ends are sealed in a pressure-resistant pipe (pressure resistance> 3MPa). The fiber membrane is placed in the center of the pipe. A layer of counter electrode metal mesh is arranged inside the pipe. A layer of polypropylene insulating mesh is arranged inside the metal mesh. The average distance between the metal mesh and the fiber membrane is 10mm. Lead wires are drawn from the fiber membrane and the metal mesh, respectively, and connected to an external DC regulated power supply.
[0026] b. Apply voltage to the hollow fiber membrane through a DC stabilized power supply, the filtration form is cross-flow filtration, the opening and closing degree of the cross-flow valve and the inlet and outlet valves are adjusted, and constant flow filtration is performed under pressure drive;
[0027] c. When the operating flux drops by 20%, stop filtration, close the outlet valve, open the inlet valve and the cross-flow valve, increase the cross-flow speed to 1.5 to 3 times the cross-flow speed during filtration, and continue to apply voltage to the hollow fiber membrane to achieve the removal process of membrane contamination.
[0028] In the above technical solution, further, in step a, the electrode metal mesh is one of titanium mesh, stainless steel mesh, and iron wire mesh; the lead wire is one of titanium wire, stainless steel wire, and iron wire.
[0029] In the above technical solution, further, in step b, the applied voltage is 0 to 10V and is not 0, preferably 1.0 to 2.5V.
[0030] In the above technical solution, further, in step b, the bias voltage on the film is -1.4 to +1.4 V vs. SCE.
[0031] In the above technical solution, further, in step b, when the pollutants in the influent water are negatively charged, a negative bias is applied to the membrane; when the pollutants in the influent water are positively charged, a positive bias is applied to the membrane.
[0032] In the above technical solution, further, in step c, the applied voltage is 0 to 10V, and is not 0, preferably 0.5 to 3.0V.
[0033] In the above technical solution, further, in step c, during backwashing, the cross flow velocity is 0.075 to 0.3 m / s, preferably 0.15 to 0.25 m / s.
[0034] The conductive carbon nanotube hollow fiber membrane for resisting membrane pollution of the present invention is not a simple combination of carbon nanotubes and polymers, but a membrane separation layer with cross-linked carbon nanotubes is constructed through secondary cross-linking of maleimide and pyrrole, and a complete conjugated structure is formed between the carbon nanotubes and the maleimide and pyrrole polymer molecules, which can greatly slow down the adhesion and retardation of pollutants on the membrane surface and in the membrane pores. At the same time, the synergistic conductive effect of carbon nanotubes and pyrrole polymers can further enhance the repulsive effect of the membrane on pollutants of the same charge under the electrochemical strengthening process conditions assisted by external voltage, greatly slow down the accumulation of membrane pollution, and enhance the anti-pollution performance of the membrane. At the same time, for a certain degree of membrane pollution accumulation after long-term operation, backwashing is not required, and the membrane pollution can be effectively removed by a simple electrochemically enhanced cross-flow flushing method.
[0035] The beneficial effects of the present invention are:
[0036] 1. The preparation process of the present invention is simple, and the required equipment and raw materials are cheap and easily available.
[0037] 2. The present invention connects carbon nanotubes to form a continuous hydrophobic structure network through secondary cross-linking of maleimide and pyrrole, thereby reducing the adhesion and retardation of pollutants on the membrane surface and in the pores. Therefore, the prepared hollow fiber membrane has excellent anti-membrane pollution ability.
[0038] 3. The hollow fiber membrane prepared by the present invention also has good electrical conductivity, and can further enhance the electrostatic repulsion effect of the membrane interface through the method of electrochemical strengthening, thereby enhancing the anti-membrane pollution performance during the filtration process and the membrane pollution removal performance during the backwashing process. The present invention effectively removes membrane pollution without backwashing through electrochemical strengthening, greatly improving the water production rate and the stability of membrane system operation, and reducing the operating cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The scanning electron microscope images of the conductive carbon nanotube hollow fiber membrane resistant to membrane fouling of Example 1, a is a scanning electron microscope image of the surface, and b is a scanning electron microscope image of the cross section;
[0040] Figure 2 The flowchart of the method for preparing the conductive carbon nanotube hollow fiber membrane resistant to membrane pollution of the present invention;
[0041] Figure 3 This is a diagram showing the anti-membrane fouling effect of the conductive carbon nanotube hollow fiber membrane of Example 1 in filtering a humic acid solution;
[0042] Figure 4 This is a diagram showing the anti-membrane fouling effect of the conductive carbon nanotube hollow fiber membrane with anti-membrane fouling in Example 1 after electrochemical coupling in filtering a humic acid solution;
[0043] Figure 5 This is a test diagram of the water contact angle of the conductive carbon nanotube hollow fiber membrane that is resistant to membrane fouling in Example 1. DETAILED DESCRIPTION
[0044] In order to better understand the technical solution of the present invention, the present invention is further described in detail by three embodiments below. However, the following embodiments are only simple examples of the present invention and are not limited to the following embodiments.
[0045] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.
[0046] Example 1
[0047] The method for preparing a conductive carbon nanotube hollow fiber membrane resistant to membrane pollution specifically comprises the following steps:
[0048] (1) Preparation of spinning solution
[0049] A certain amount of purified carbon nanotubes with an outer diameter of 15 to 20 nm, N-(4-anilinophenyl)maleimide crosslinker and polyvinyl butyral ester are added to N,N-dimethylacetamide, and the total mass fraction of the three solutes is 10%, and then quickly pre-stirred at room temperature. Next, in a constant temperature oil bath at 80°C, continue to stir evenly and slowly add a certain amount of polyvinyl butyral ester and N-(4-anilinophenyl)maleimide crosslinker again, and the total mass fraction of the three solutes is increased to 30%. Stirring is continued until they are completely dissolved to obtain a spinning solution;
[0050] (2) Preparation of basement membrane
[0051] The spinning solution was cooled to 25°C and then vacuum degassed. Water was used as the spinning core solution and the spinning solution was used as the spinning shell solution. The core solution and the shell solution were simultaneously passed through the spinning head at a flow rate ratio of 2:1. The solution entered a 50°C aqueous solution coagulation bath containing 50% acetonitrile and was then pulled into a membrane at a pulling speed of 0.2 m / min. The membrane fibers were then taken out of the coagulation bath and dried at 80°C to obtain a base membrane.
[0052] (3) Pretreatment of base film by immersion and pulling
[0053] A 2.5% by mass ferric chloride acetonitrile solution was prepared, and the base film was immersed in the solution at room temperature. After immersion, the immersed base film was pulled into the air using a low-speed pulling machine at a pulling speed of 1 mm / s, and then dried for 40 minutes to obtain a base film containing an oxide layer;
[0054] (4) Secondary crosslinking of conductive polymer and maleimide crosslinker
[0055] N-(4-anilinophenyl)maleimide and pyrrole monomer are mixed to prepare a mixed solution with a mass fraction of N-(4-anilinophenyl)maleimide of 2%. A quartz cover is used to seal the dried base film containing an oxide layer on the top of the mixed solution without contacting the base film with the mixed solution. The base film is placed in a vacuum drying oven and polymerized and cross-linked at 90° C. for 120 minutes. The base film is taken out after being cooled to room temperature, and then immersed in a 50% acetonitrile solution for 5 minutes. Finally, the base film is dried in air and collected to obtain a conductive carbon nanotube hollow fiber membrane.
[0056] The average pore size of the hollow fiber membrane prepared in Example 1 is 2 nm, and the conductivity is 60 S / m. Figure 1 The scanning electron microscope images show that a hollow fiber structure separation membrane was successfully prepared, the membrane pores are uniform, the carbon nanotubes are cross-linked, and the surface is intact and free of defects.
[0057] Figure 5This is a water contact angle test diagram of the hollow fiber membrane prepared in Example 1. Figure 5 It can be seen that the water contact angle of the hollow fiber membrane is 124°, which has good hydrophobicity.
[0058] Example 2
[0059] The method for preparing a conductive carbon nanotube hollow fiber membrane resistant to membrane pollution specifically comprises the following steps:
[0060] (1) Preparation of spinning solution
[0061] Add a certain amount of purified carbon nanotubes with an outer diameter of 5 to 10 nm, N-(4-anilinophenyl)maleimide crosslinker and polyvinyl butyral ester to N,N-dimethylformamide, the total mass fraction of the three solutes is 15%, then quickly pre-stir evenly at room temperature, then continue to stir evenly in a 100°C constant temperature oil bath and slowly add a certain amount of polyvinyl butyral ester and N-(4-anilinophenyl)maleimide crosslinker again, the total mass fraction of the three solutes is increased to 35%, continue stirring until they are completely dissolved, and obtain a spinning solution;
[0062] (2) Preparation of basement membrane
[0063] The spinning solution was cooled to 30°C and then vacuum degassed. Water was used as the spinning core solution and the spinning solution was used as the spinning shell solution. The core solution and the shell solution were simultaneously passed through the spinning head at a flow rate ratio of 1:1. The solution entered a 50°C aqueous solution coagulation bath containing 70% acetonitrile and was then pulled into a membrane at a pulling speed of 0.1 m / min. The membrane fibers were then taken out of the coagulation bath and dried at 80°C to obtain a base membrane.
[0064] (3) Pretreatment of base film by immersion and pulling
[0065] A 5% by mass ferric chloride acetonitrile solution was prepared, and the base film was immersed in the solution at room temperature. After immersion, the immersed base film was pulled into the air using a low-speed pulling machine at a pulling speed of 1 mm / s, and then dried for 30 minutes to obtain a base film containing an oxide layer;
[0066] (4) Secondary crosslinking of conductive polymer and maleimide crosslinker
[0067] N-(4-anilinophenyl)maleimide and pyrrole monomer are mixed to prepare a mixed solution with a mass fraction of N-(4-anilinophenyl)maleimide of 2%. A quartz cover is used to seal a dried base film containing an oxide layer on the top of the mixed solution without contacting the base film with the mixed solution. The base film is placed in a vacuum drying oven and polymerized and cross-linked at 100° C. for 180 minutes. The base film is taken out after being cooled to room temperature, and then immersed in a 60% acetonitrile solution for 10 minutes. Finally, the base film is dried in the air and collected to obtain a conductive carbon nanotube hollow fiber membrane that is resistant to membrane pollution.
[0068] The average pore size of the hollow fiber membrane prepared in Example 2 is 1.2 nm, and the conductivity is 70 S / m.
[0069] Example 3
[0070] The method for preparing a conductive carbon nanotube hollow fiber membrane resistant to membrane pollution specifically comprises the following steps:
[0071] (1) Preparation of spinning solution
[0072] A certain amount of purified carbon nanotubes with an outer diameter of 25 to 30 nm, N-phenylmaleimide crosslinker and polyvinyl butyral ester are added to N,N-dimethylformamide, and the total mass fraction of the three solutes is 8%, and then quickly pre-stirred at room temperature. Next, in a constant temperature oil bath at 80°C, continue to stir evenly and slowly add a certain amount of polyvinyl butyral ester and N-phenylmaleimide crosslinker again, and the mass fraction of the solute is increased to 25%. Stirring is continued until it is completely dissolved to obtain a spinning solution;
[0073] (2) Preparation of basement membrane
[0074] The spinning solution was cooled to 25°C and then vacuum degassed. Water was used as the spinning core solution and the spinning solution was used as the spinning shell solution. The core solution and the shell solution were simultaneously passed through the spinning head at a flow rate ratio of 1.5:1. The solution entered a 50°C aqueous solution coagulation bath containing 30% acetonitrile and was then pulled into a membrane at a pulling speed of 0.2 m / min. The membrane fibers were then taken out of the coagulation bath and dried at 60°C.
[0075] (3) Pretreatment of base film by immersion and pulling
[0076] A 2.5% by mass ferric chloride acetonitrile solution was prepared, and the base film was immersed in the solution at room temperature. After immersion, the immersed base film was pulled into the air using a low-speed pulling machine at a pulling speed of 2 mm / s, and then dried for 60 minutes;
[0077] (4) Secondary crosslinking of conductive polymer and maleimide crosslinker
[0078] N-(4-anilinophenyl)maleimide and pyrrole monomer are mixed to prepare a mixed solution with a mass fraction of N-(4-anilinophenyl)maleimide of 2%. A quartz cover is used to seal a dried base film containing an oxide layer on the top of the mixed solution without contacting the base film with the mixed solution. The base film is placed in a vacuum drying oven and polymerized and cross-linked at 80° C. for 120 minutes. The base film is taken out after being cooled to room temperature, and then immersed in a 30% acetonitrile solution for 10 minutes. Finally, the base film is dried in the air and collected to obtain a conductive carbon nanotube hollow fiber membrane that is resistant to membrane pollution.
[0079] The average pore size of the hollow fiber membrane prepared in Example 3 is 8 nm, and the conductivity is 42 S / m.
[0080] Application Example 1
[0081] The hollow fiber membrane prepared in Example 1 was used as a membrane electrode and electrochemically coupled to treat water. -1 The humic acid solution is used as the raw liquid to be treated, and specifically comprises the following steps:
[0082] (1) Encapsulating a conductive carbon nanotube hollow fiber membrane that resists membrane fouling in a membrane module, wherein the hollow fiber membrane serves as a working electrode, and both ends are sealed in a pressure-resistant pipe fitting, wherein the hollow fiber membrane is placed in the center of the pipe fitting, and a layer of a counter electrode titanium mesh is arranged inside the pipe fitting, and a layer of a polypropylene insulating mesh is arranged inside the titanium mesh, wherein the average distance between the titanium mesh and the fiber membrane is 10 mm, and titanium wires are respectively led out from the fiber membrane and the titanium mesh and connected to an external DC regulated power supply;
[0083] (2) Under the conditions of 100 kPa operating pressure and 0.1 m / s cross-flow velocity, the hollow fiber membrane has good anti-fouling performance, and the flux decline rate during the stable operation period is 0.08 L m -2 h -2 bar -1 When a voltage of 2.0 V was applied to the hollow fiber membrane, the anti-fouling performance of the hollow fiber membrane was further improved, and the flux decline rate was further reduced to 0.02 L m -2 h -2 bar -1 , the removal rate of humic acid is 99.7%;
[0084] (3) When the operating flux dropped by 20%, the filtration was stopped, the cross-flow velocity was increased to 0.2 m / s, a voltage of 2.0 V was applied, and the membrane fouling removal rate was 100%.
[0085] Application Example 2
[0086] The hollow fiber membrane prepared in Example 2 was used as a membrane electrode and coupled with electrochemical treatment to treat water. Surface water was used as the treated stock solution, and its permanganate index was 4.8 mg L -1, turbidity is 1.6NTU, specifically including the following steps:
[0087] (1) Encapsulating a conductive carbon nanotube hollow fiber membrane that resists membrane fouling in a membrane module, wherein the hollow fiber membrane serves as a working electrode, and both ends are sealed in a pressure-resistant pipe fitting, wherein the hollow fiber membrane is placed in the center of the pipe fitting, and a layer of a counter electrode titanium mesh is arranged inside the pipe fitting, and a layer of a polypropylene insulating mesh is arranged inside the titanium mesh, wherein the average distance between the titanium mesh and the fiber membrane is 10 mm, and titanium wires are respectively led out from the fiber membrane and the titanium mesh and connected to an external DC regulated power supply;
[0088] (2) Under the conditions of 100 kPa operating pressure and 0.08 m / s cross-flow velocity, the hollow fiber membrane has good anti-fouling performance, and the flux decline rate during the stable operation period is 0.04 L m -2 h -2 bar -1 When the voltage applied to the hollow fiber membrane was 2.0 V, the anti-fouling performance of the hollow fiber membrane was further improved, and the flux decline rate was further reduced to 0.01 L m -2 h - 2 bar -1 , the removal rate of permanganate index is 97.5%;
[0089] (3) When the operating flux dropped by 20%, filtration was stopped, the cross-flow velocity was increased to 0.16 m / s, a voltage of 2.0 V was applied, and the membrane fouling removal rate was 100%.
[0090] Application Example 3
[0091] The hollow fiber membrane prepared in Example 3 was used as a membrane electrode and coupled with electrochemical treatment to treat water. The secondary biochemical effluent of a chemical wastewater was used as the raw liquid to be treated. Its COD was 72 mg L -1 , specifically including the following steps:
[0092] (1) Encapsulating a conductive carbon nanotube hollow fiber membrane that resists membrane fouling in a membrane module, wherein the hollow fiber membrane serves as a working electrode, and both ends are sealed in a pressure-resistant pipe fitting, wherein the hollow fiber membrane is located at the center of the pipe fitting, and a layer of a counter electrode titanium mesh is arranged inside the pipe fitting, and a layer of a polypropylene insulating mesh is arranged inside the titanium mesh, wherein the average distance between the titanium mesh and the fiber membrane is 10 mm, and titanium wires are respectively led out from the fiber membrane and the titanium mesh and connected to an external DC regulated power supply;
[0093] (2) Under the conditions of 100 kPa operating pressure and 0.15 m / s cross-flow velocity, the hollow fiber membrane has good anti-fouling performance, and the flux decline rate during the stable operation period is 0.12 L m -2 h -2 bar -1When the voltage applied to the hollow fiber membrane was 2.5 V, the anti-fouling performance of the hollow fiber membrane was further improved, and the flux decline rate was further reduced to 0.04 L m -2 h - 2 bar -1 , the effluent COD reaches 34mg L -1 , the COD removal rate is 52.8%;
[0094] (3) When the operating flux dropped by 20%, the filtration was stopped, the cross-flow velocity was increased to 0.3 m / s, a voltage of 2.5 V was applied, and the membrane fouling removal rate was 100%.
[0095] The embodiments described above are only typical embodiments of the present invention and do not constitute improper limitations on the present invention. Therefore, all obvious modifications described in the scope of the patent application of the present invention and other modifications that do not deviate from the essence of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a conductive carbon nanotube hollow fiber membrane that is resistant to membrane pollution, characterized in that: The steps include: (1) Preparation of spinning solution Add purified carbon nanotubes, maleimide crosslinker and polyvinyl butyral ester to the solvent, stir evenly at room temperature to obtain solution A, then add polyvinyl butyral ester and maleimide crosslinker under the condition of constant temperature oil bath of 80-100° C., stir until completely dissolved, and obtain spinning solution; (2) Preparation of basement membrane Using water as the spinning core liquid and the spinning liquid as the spinning shell liquid, the core liquid and the shell liquid are controlled to pass through the spinning head at the same time, and then enter the coagulation bath to be pulled into a film, and then dried to obtain a base film; (3) Pretreatment of base film by immersion and pulling At room temperature, the base film is immersed and pulled in an acetonitrile solution of ferric chloride or ferric sulfate, and after drying, a base film containing an oxide layer is obtained; (4) Secondary crosslinking of conductive polymer and maleimide crosslinker The maleimide crosslinking agent is mixed with the pyrrole monomer to obtain a mixed solution. A base film containing an oxide layer is placed on the mixed solution by a gas phase polymerization method, and the base film is placed in a vacuum drying oven. The base film is polymerized and crosslinked at 80 to 100° C. for 120 to 180 minutes. The base film is immersed in an acetonitrile solution after cooling, and a conductive carbon nanotube hollow fiber membrane is obtained after drying.
2. The preparation method according to claim 1, characterized in that: In step (1), the purified carbon nanotubes are single-walled carbon nanotubes or multi-walled carbon nanotubes, with a purity of >96% and a content of oxygen-containing functional groups less than 0.5 wt %; The maleimide crosslinking agent is one or a mixture of maleimide, N-(4-anilinophenyl)maleimide, N-phenylmaleimide, N,N′-(1,3-phenylene)bismaleimide, N,N′-(4,4′-methylenediphenyl)bismaleimide; The molecular weight of the polyvinyl butyral ester is 20000 to 300000; The solvent is one of N,N-dimethylformamide and N,N-dimethylacetamide or a mixture of the two.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass fraction of the solute in the solution A is 5 to 15%, and the mass fraction of the solute in the spinning solution is 20 to 50%.
4. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the purified carbon nanotubes, polyvinyl butyral ester and maleimide in the spinning solution is 40-100:100:5-10.
5. The preparation method according to claim 1, characterized in that: In step (2), the coagulation bath is 50-100% acetonitrile solution, and the temperature of the coagulation bath is 25-60° C.; The flow rate ratio of the core liquid to the shell liquid is 0.5 to 3:1; The pulling speed is the same as the shell liquid extrusion speed, which is 0.2-1m / min; The drying temperature is 80-100°C.
6. The preparation method according to claim 1, characterized in that: In step (3), the mass fraction of the solute in the acetonitrile solution of ferric chloride or ferric sulfate is 2 to 5%; The base film is immersed in the acetonitrile solution for 5 to 20 minutes, and the pulling speed after immersion is 1 to 3 mm / s; The drying time is 30 to 120 minutes.
7. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of the pyrrole monomer solution to the base film is 0.25 to 1:1; In the mixed solution, the mass fraction of the maleimide cross-linking agent is 0.5-2%; The maleimide crosslinking agent is one or a mixture of maleimide, N-(4-anilinophenyl)maleimide, N-phenylmaleimide, N,N′-(1,3-phenylene)bismaleimide, N,N′-(4,4′-methylenediphenyl)bismaleimide; The degree of vacuum in the polymerization and cross-linking environment is >95%; The immersion time is 5 to 10 minutes; The mass fraction of the acetonitrile solution is 50-100%.
8. A conductive carbon nanotube hollow fiber membrane resistant to membrane fouling obtained by the preparation method according to any one of claims 1 to 7.
9. A water treatment method using a conductive carbon nanotube hollow fiber membrane coupled with electrochemistry, characterized in that: The hollow fiber membrane described in claim 8 is used as a membrane electrode. During the water treatment process, a voltage is applied to the hollow fiber membrane, the voltage is 0 to 10 V and is not 0, the filtration form is cross-flow filtration, and the cross-flow velocity is 0.05 to 0.1 m / s; during the backwashing process, a voltage is applied to the hollow fiber membrane, the voltage is 0 to 10 V and is not 0, and the cross-flow velocity is 1.5 to 3 times the flow velocity during filtration.
Citation Information
Patent Citations
Preparation method of nanofiltration membrane and nanofiltration membrane prepared thereby
CN114642971A
Preparation method of conductive carbon nanotube-polyvinylidene fluoride composite hollow fiber membrane and electrochemical coupling membrane separation assembly
CN116571101A